ANALISIS BIFURKASI DINAMIKA POPULASI PENGRAJIN SONGKET DALAM MENJAGA EKSISTENSI KERAJINAN SONGKET PANDAI SIKEK - Adryan, Muhammad Rizki; Winanda, Rara Sandhy (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2024)
Songket is called the "Queen of Textiles" because of its beauty and luxury, combined with the sparkle of gold and silver threads, is one type of textile. However, the selling value and economic potential of songket in Nagari Pandai Sikek are not in line with the number of craftsmen. This phenomenon was analyzed using mathematical modeling, focusing on local stability. As a result, three equilibrium points were found. The first equilibrium point describes a state in which there are only potential craftsmen. Meanwhile, the second equilibrium point indicates the presence of potential craftsmen, proficient craftsmen aged 18-35 years, and professional craftsmen, but no proficient craftsmen over 35 years old. At the third equilibrium point, there are potential craftsmen, proficient craftsmen over 35 years old, and professional craftsmen, but there are no proficient craftsmen aged 18-35 years. Bifurcation analysis shows that if the value is ,, then the songket craftsmen can still survive. However, if it is  the songket craftsmen will experience rapid decline and will slowly become extinct